2021
DOI: 10.1101/2021.01.04.425272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ERK signaling licenses SKN-1A/NRF1 for proteasome production and proteasomal stress resistance

Abstract: The ubiquitin-proteasome system is vital for cell growth and homeostasis, but for most cancers proteasomal inhibition has not been effective as a therapy. Normal and cancer cells adapt to proteasomal stress through an evolutionarily conserved recovery response, in which the transcription factor NRF1 upregulates proteasome subunit genes. Starting with a C. elegans screen to identify regulators of the recovery response, here we show that this response depends upon phosphorylation of NRF1 on a single residue by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…We wanted to determine if impairment of proteasome function can induce the oomycete recognition response (ORR). We performed RNAseq analysis of ddi-1(icb156) mutants versus wild-type controls and compared the set of up-regulated genes with those previously reported for inhibition of proteasomal activity by BTZ drug treatment [35], oomycete recognition response [3] and skn-1a loss-of-function [35]. A significant overlap was identified between all these datasets (Figure 1D, S1B, and supplementary table S1).…”
Section: Mutants In the Proteasome Surveillance Pathway Show Constitu...mentioning
confidence: 79%
“…We wanted to determine if impairment of proteasome function can induce the oomycete recognition response (ORR). We performed RNAseq analysis of ddi-1(icb156) mutants versus wild-type controls and compared the set of up-regulated genes with those previously reported for inhibition of proteasomal activity by BTZ drug treatment [35], oomycete recognition response [3] and skn-1a loss-of-function [35]. A significant overlap was identified between all these datasets (Figure 1D, S1B, and supplementary table S1).…”
Section: Mutants In the Proteasome Surveillance Pathway Show Constitu...mentioning
confidence: 79%
“…If this were the case, then induction would not be affected by proteasome impairment via bortezomib (BTZ) drug treatment [ 35 ]. To determine if impairment of proteasome function can induce the ORR, we performed RNAseq analysis of ddi-1(icb156) mutants versus wild-type controls and compared the set of up-regulated genes with those previously reported for inhibition of proteasomal activity by BTZ drug treatment [ 36 ], oomycete recognition response [ 3 ], and skn-1a loss-of-function [ 36 ]. A significant overlap was identified between all these datasets (Figs 1C and S1C , and S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Dysfunction of this TF is associated with glucose metabolism reprogramming via AMPK signaling (Yang et al, 2021). NFE2L1 also upregulates expression of proteasomal genes in an ERK-signaling dependent manner (Zhang et al, 2021b), which is suggested to contribute to the development of neurodegenerative diseases (Lee et al, 2011).…”
Section: Supplementary Informationmentioning
confidence: 99%